Modern Slavery And Forced Labour: An Overview Of International Law, The Malaysian Law And Islamic Law Perspectives - Hendun Abd. Rahman Shah; Baidar Mohammed Mohammed Hasan; Haziman Muhamad Ahmad; Norfadhilah Mohamad Ali (UIN JAKARTA, 2024)
The paper aims to provide an overview of modern slavery and forced labour under international, Malaysian and Islamic law perspectives. It employs doctrinal methods which mainly focus on library-based research through legal analysis and review of past works, as well as the historical and explanatory method that help explain the views of commentators and scholars in international and Islamic law. It then connects ideas to understand the issue in the local context. This paper concludes that there is a lack of a clear definition of modern slavery universally, which makes it difficult to identify whether the exploitation of the workers, is amounting to merely a violation of rights or to some extent is amounting to slavery or forced labour or trafficking of persons as demarcated by either International law or the Malaysian law. Nevertheless, Islamic law has not given much emphasis on definition, rather it provides remedy and guidelines in protecting workers from oppression and slavery such as regulating the relationship between the employer and the worker according to the precise legal criteria to guarantee fulfilment of rights and non-aggression so that labour does not turn into a new arena of modern slavery.